Predictors of acute throat or esophageal patient reported pain during radiation therapy for head and neck cancer. (November 2018) - Gay, Hiram A.; Oh, Jung Hun; Apte, Aditya P.; Daly, Mackenzie D.; Adkins, Douglas R.; Rich, Jason; Oppelt, Peter J.; Dyk, Pawel T.; Mullen, Daniel F.; Eschen, Laura; Chin, Re-I.; Nussenbaum, Brian; et al.
Abstract: Background and purpose: Acute pain during weekly radiotherapy (RT) to the head and neck is not well characterized. We studied dose-volume metrics and clinical variables that are plausibly associated with throat or esophageal pain as measured with a weekly questionnaire during RT. Materials and methods: We prospectively collected weekly patient-reported outcomes from 122 head and neck cancer patients during RT. The pain score for each question consisted of a four-level scale: none (0), mild (1), moderate (2), and severe (3). Univariate and multivariate ordinal logistic regression analyses were performed to investigate associations between both esophageal and throat pain and clinical as well as dosimetric variables. Results: In multivariate analysis, age was significantly associated with both types of pain, leading to odds ratio (OR) = 0.95 (p = 0.008) and OR = 0.95 (p = 0.007) for esophageal and throat pain, respectively. For throat pain, sex (OR = 4.12; p = 0.010), with females at higher risk, and fractional organ at risk (OAR) mean dose (OR = 3.30; p = 0.014) were significantly associated with throat pain. Conclusions: A fractional OAR mean dose of 1.1 Gy seems a reasonable cutoff for separating no or mild pain from moderate to severe esophageal and throat pain. Younger patients who received RT experienced more esophageal and throat pain. Females experienced more throat pain, but not esophageal pain.